Dynamic bimodal changes in CpG and non-CpG methylation genome-wide upon CGGBP1 loss-of-function - Patel, Divyesh (BMC Res Notes, 2018)
OBJECTIVES: Although CpG methylation is well studied, mechanisms of non-CpG methylation in mammals remains elusive. Studying proteins with non-CpG cytosine methylation-sensitive DNA-binding, such as human CGGBP1, can unveil cytosine methylation regulatory mechanisms. Here we have resequenced a published genome-wide bisulfite sequencing library and analyzed it at base level resolution. CpG, CHG and CHH (where H is any nucleotide other than G) methylation states in non-targeting or CGGBP1-targeting shmiR lentivirus-transduced cells have been analyzed to identify how CGGBP1 regulates CpG and non-CpG methylation. RESULTS: We report that CGGBP1 acts as a dynamic bimodal balancer of methylation. Both gain and loss of methylation observed upon CGGBP1 depletion were spatially overlapping at annotated functional regions and not identifiable with any sequence motifs but clearly associated with GC-skew. CGGBP1 depletion caused clustered methylation changes in cis, upstream of R-loop forming promoters. This was complemented by clustered occurrences of methylation changes in proximity of transcription start sites of known cytosine methylation regulatory genes, altered expression of which can regulate cytosine methylation in trans. Despite low coverage, our data provide reliable estimates of the spectrum of methylation changes regulated by CGGBP1 in all cytosine contexts genome-wide through a combination of cis and trans-acting mechanisms. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-018-3516-1) contains supplementary material, which is available to authorized users.